2020
DOI: 10.4025/actasciagron.v43i1.49054
|View full text |Cite
|
Sign up to set email alerts
|

Training systems, rootstocks and climatic conditions influence quality and antioxidant activity of ‘BRS Cora’ grape

Abstract: Environmental and production factors might affect grapevine physiology. Estimating these effects is essential for planning the harvest and predicting the quality of grapes. The aim of this study was to characterize the quality and antioxidant potential of ‘BRS Cora’ grapes with different training systems and rootstocks in production cycles of the second half of the year under tropical conditions. The experimental design was randomized blocks with sub-subdivided plots over time. Three training systems and two r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 24 publications
2
3
0
Order By: Relevance
“…The highest antioxidant activity (AA) in the skins (measured by the DPPH method) was found for the Beta variety (4.34 mg TE/g f.m.). These results correspond with the study of Costa and Ferreira (2021) [ 24 ], who reported that fruits of the BRS Cora cultivar (which are similar in color at maturity to Beta) exhibit AA ranging from 3.6 to 4.64 mg TE/g f.m. We also found the highest AA value for fresh fruit pulp of white Michigan (1.89 mg TE/g f.m.…”
Section: Resultssupporting
confidence: 92%
“…The highest antioxidant activity (AA) in the skins (measured by the DPPH method) was found for the Beta variety (4.34 mg TE/g f.m.). These results correspond with the study of Costa and Ferreira (2021) [ 24 ], who reported that fruits of the BRS Cora cultivar (which are similar in color at maturity to Beta) exhibit AA ranging from 3.6 to 4.64 mg TE/g f.m. We also found the highest AA value for fresh fruit pulp of white Michigan (1.89 mg TE/g f.m.…”
Section: Resultssupporting
confidence: 92%
“…The differentiated response between harvest seasons confirms the results reported by Costa et al (2021), who studied grapevine cultivar 'BRS Cora' in a tropical climate and correlated environmental conditions with the accumulation of phenolics, which caused differences in the antioxidant activity of the grapes. Similar to total extractable polyphenols, grapevines grafted on 'IAC 766' trained to lyre produced grapes with higher antioxidant activity in season 2, with a higher solar radiation rate, according to the ABTS •+ capture method.…”
Section: Phenolic Compounds and Antioxidant Activitysupporting
confidence: 88%
“…The adoption of this rootstock, which is widely recognized for its high vigor in tropical conditions, resulted in the highest soluble solids contents in berries. This might be explained by the higher uptake of light provided by the systems lyre and OTS systems, validating that the rootstock influences bunch quality even if responses vary according to the climatic conditions, scion cultivar, and trellis system adopted (Ferreira et al, 2019;Costa et al, 2021).…”
Section: Physical and Chemical Characteristicsmentioning
confidence: 78%
See 2 more Smart Citations